Analgesic and Sedative Effects of Different Doses of Dexmedetomidine Combined with Butorphanol in Continuous Analgesia after a Cesarean Section - Liu, Hui; Wang, Yalin; Li, Fulong; Ren, Wei; Yuan, Li (Frontiers in Surgery, 2022)
Objective The present study is designed to study the analgesic and sedative effect of different doses of dexmedetomidine combined with butorphanol in continuous analgesia after a cesarean section. Methods A total of 60 puerperae undergoing a cesarean section recruited from a single center were divided into three groups according to the postoperative continuous analgesia protocol: control group (100 mL of normal saline containing 10 µg/kg fentanyl and 0.25 mg of palonosetron, 2 mL/h for continuous analgesia for 48 h), DB1 group (100 mL of normal saline containing 1.0 µg/kg dexmedetomidine, 4 mg of butorphanol, 10 µg/kg fentanyl, and 0.25 mg of palonosetron, 2 mL/h for continuous analgesia for 48 h), and DB2 group (100 mL normal saline containing 2.0 µg/kg dexmedetomidine, 4 mg of butorphanol, 10 µg/kg fentanyl, and 0.25 mg of palonosetron, 2 mL/h for continuous analgesia for 48 h). We compared the blood pressure, heart rate, oxygen saturation, VAS score, Ramsay score, and adverse reactions of puerperae among the three groups after surgery. Results The baseline data all have no significant difference in the three groups (p > 0.05). Compared with those in the control group, the systolic blood pressure, diastolic blood pressure, heart rate, and VAS score of the puerperae in the DB1 group and DB2 group were significantly decreased at 6, 24, and 48 h (P < 0.05), while the Ramsay scores of the puerperae in DB1 group and DB2 group were significantly increased at 6, 24, and 48 h (p < 0.05). At the same time, the systolic blood pressure, diastolic blood pressure, heart rate, and VAS score of the puerperae in the DB2 group were significantly lower than those in the DB1 group (P < 0.05), while the Ramsay scores of the puerperae in DB2 group were significantly higher than those in the DB1 group (P < 0.05). Also, there is no significant difference in oxygen saturation and adverse reactions of puerperae among the three groups after surgery (p > 0.05). Conclusion Dexmedetomidine combined with butorphanol can improve the analgesic and sedative effects in continuous analgesia after a cesarean section, and the analgesic and sedative effects of dexmedetomidine in the high-dose group are better than those in the low-dose group.